The Developing Microbiome From Birth to 3 Years: The Gut-Brain Axis and Neurodevelopmental Outcomes - Laue, Hannah E.; Coker, Modupe O.; Madan, Juliette C. (Frontiers in Pediatrics, 2022)
The volume and breadth of research on the role of the microbiome in neurodevelopmental and neuropsychiatric disorders has expanded greatly over the last decade, opening doors to new models of mechanisms of the gut-brain axis and therapeutic interventions to reduce the burden of these outcomes. Studies have highlighted the window of birth to three years as an especially sensitive window when interventions may be the most effective. Harnessing the powerful gut-brain axis during this critical developmental window clarifies important investigations into the microbe-human connection and the developing brain, affording opportunities to prevent rather than treat neurodevelopmental disorders and neuropsychiatric illness. In this review, we present an overview of the developing intestinal microbiome in the critical window of birth to age 3 years and its prospective relationship with neurodevelopment, with particular emphasis on immunological mechanisms. Next, the role of the microbiome in neurobehavioral outcomes (such as autism, anxiety and attention-deficit hyperactivity disorder (ADHD) as well as cognitive development are described. In these sections, we highlight the importance of pairing mechanistic studies in murine models with large scale epidemiological studies that aim to clarify typical health promoting microbiome in early life across varied populations in comparison to dysbiosis. The microbiome is an important focus in human studies because it is so readily alterable with simple interventions, and we briefly outline what is known about microbiome targeted interventions in neurodevelopmental outcomes. More novel examinations of known environmental chemicals that adversely impact neurodevelopmental outcomes and the potential role of the microbiome as a mediator or modifier are discussed. Finally, we look to the future and emphasize the need for additional research to identify populations that are sensitive to alterations in their gut microbiome and clarify how interventions might correct and optimize neurodevelopmental outcomes.